Trends and Determinants of Unmet Need For Contraception among Married Female Youth in Nepal - Lamichhane, Kamala Devi (Tribhuvan University Journal, 2021)
The unmet need for contraception continues to be high among married female youth in Nepal even though the accessibility of contraceptive methods and people's consciousness has been enhanced significantly. This study intends to identify the trends of unmet need for contraception for 15 years and its determinants. Because the trends of unmet need for contraception and its influencing factors among female youth are not exclusively studied in Nepal. The main data sources for the study are Nepal Demographic and Health Surveys (NDHS) 2001, 2006, 2011 and 2016. The sample sizes from the NDHSs are 2,573 in 2,001; 2,389 in2006; 2,552 in 2011; and 2,287 in 2016. Logistic regression analysis is applied to examine the factors that affect the unmet needs. During 15 years, the unmet need for contraception has decreased marginally in Nepal but is quite high (32%) among married female youth especially adolescents. There is only a nominal percentage (2.1) point decline from 34.1 in 2001 to 32.2 percent in 2016. Socio demographic factors such as married female youth's age, age of cohabitation, total living children, spousal separation, youths’ education, their husbands’ occupation, and wealth status are the evident determinants of the unmet need for contraception among female youth in Nepal. The nation’s family planning program has to be made to communicate effectively the needs of various specific groups: youth couples who are living together, educated, Muslims, poor, and living in rural areas where unmet need is high.